Kualitas Yoghurt Buah Naga Merah (Hylocereus Polyrhizus) Pada Konsentrasi Starter Dan Lama Fermentasi Yang Berbeda - Nurpitayanti, Dian, Efri Roziaty S.si.M.si (2017)
ogurt is a product processed from milk fermented beverage by lactic acid bacteria. Dragon fruit contains bioactive substances that are beneficial to the body, antioxidants, dietary fiber (pectin), and minerals. This study aims to determine the quality test of red dragon fruit yoghurt (Hylocereus polyrhizus) at different concentrations and fermentation time. The method used was experimental research with complete randomized design (RAL) with two factors. Factor I was the concentration of 4%, 6%, and 8% plain yoghurt starter. Factor II is fermentation duration 19 hours, 21 hours, and 23 hours. The results showed that the concentration of starter and fermentation duration influenced the quality of red dragon fruit yoghurt. The best red dragon fruit yoghurt is P2R2 (6% starter and 21 hours fermentation duration), P2R3 (6% starter and 23 hours fermentation time) and P3R1 (8% starter and 19 hours fermentation duration) ie thick, pink texture / Pink, typical yoghurt aroma, sour taste and acceptable power. Keywords : red dragon fruit, yogurt, starter yoghurt plain, long fermentation